Transient dynamics of magneto-optic rotation with elliptically polarized light - Binbin Zhao; Junjian Tang; Lin Li; Yaohua Zhang; Yueyang Zhai (Results in Physics, 2024)
In this paper, we analyze the transient behavior of nonlinear magneto-optical rotation in a 87Rb vapor cell. Our focus is on optimizing the optical rotation signal by identifying influential factors. We investigate the impact of cell temperature on alkali atom density and consider characteristics of the light field, such as polarization direction, frequency, intensity, and beam diameter. Low scanning magnetic field rates produce the usual absorption signal, whereas high rates show an asymmetric transient response with oscillatory decay. To further investigate this phenomenon, we evaluate signal amplitude and resonant peaks along the x-, y-, and z-axis directions. Notably, we establish a one-dimensional quadratic equation that describes the relationship between magnetic field scan rate and signal amplitude/peak value. Our findings facilitate the quick evaluation of cell performance, provide insights into the dynamics of ground-state coherence generation, and have potential applications in detecting transient spin coupling or monitoring magnetic fields.